Surveillance and response of hepatitis B in Hong Kong Special Administrative Region, 1988-2014 - Ada Wai-Chi Lin; Ka-hing Wong (World Health Organization Regional Office for the Western Pacific, 2016)
The World Health Organization (WHO) Western Pacific Region with an estimated 160 million chronic hepatitis B virus (HBV) carriers in 2007 bears a significant burden of HBV-related mortality and morbidity. Most Member States in the region have an estimated chronic HBV infection proportion of more than 8% in their adult population, which is the highest worldwide. The WHO Regional Office for the Western Pacific published the first Regional Plan for Hepatitis B Control in January 2003. This plan is updated periodically with a consistent ultimate goal of achieving a chronic HBV infection rate of less than 1% in the region. Viral hepatitis is a statutorily notifiable disease in Hong Kong Special Administrative Region (SAR). The Central Notification Office of the Department of Health receives notifications with pre-defined case definitions. In July 2011, Hong Kong SAR was verified by the WHO Regional Office for the Western Pacific as having successfully achieved the goal of hepatitis B control. Liver cancer was the third leading cause of cancer death in Hong Kong SAR in 2012, and evidence showed that 75-80% of liver cancer cases were related to chronic HBV infection. This report reviews the surveillance data of HBV infections in Hong Kong SAR from 1988 to 2014 and discusses the responses and existing gaps to achieve the WHO goal in the local context.